1998
DOI: 10.2807/esm.03.12.00101-en
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of mumps associated with poor vaccine efficacy - Oporto Portugal 1996

Abstract: Vaccination against mumps in Portugal began in 1987, with the introduction of the combined measles, mumps, and rubella vaccine (MMR) in the national vaccination programme (Programa Nacional de Vacinação: PNV) for both sexes at 15 months. In November 1990,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…12 Our study confirms the findings of other researchers of the low protection conferred by the Rubini vaccine strain. The vaccine efficacy of the Rubini strain mumps vaccine on our Asian population was K55.3% whilst that in other studies [4][5][6][7][8]10,11 conducted in the European population ranged from K4 to 40%.…”
Section: Discussionmentioning
confidence: 84%
“…12 Our study confirms the findings of other researchers of the low protection conferred by the Rubini vaccine strain. The vaccine efficacy of the Rubini strain mumps vaccine on our Asian population was K55.3% whilst that in other studies [4][5][6][7][8]10,11 conducted in the European population ranged from K4 to 40%.…”
Section: Discussionmentioning
confidence: 84%
“…A number of studies demonstrated substantially lower rates of seroconversion and effectiveness than the Jeryl-Lynn and Urabe AM9. Based on these data, WHO recommended that the Rubini strain vaccine NOT be used in national immunization programs [26,29]. A replacement for the Rubini with a more potent vaccine strain was progressing by the same producer however, this effort was discontinued immaturely.…”
Section: VIImentioning
confidence: 99%
“…Estos brotes afectaban principalmente a poblaciones susceptibles: personas no vacunadas o grupos de edad (de 15 a 23 años) que no habían tenido exposición al virus natural y tampoco estaban vacunados [14][15][16][17] . Sin embargo, ha habido también brotes en poblaciones con alta cobertura vacunal en las que se cuestionaba la efectividad de la cepa empleada para la vacunación, como en Suiza, Portugal, o España [18][19][20] . Los estudios de los brotes en estos países apuntaban hacia una escasa efectividad de la vacunación con el componente antiparotidítico de la cepa Rubini.…”
Section: Introductionunclassified